Hubungan antara Karakteristik Calon Pengantin Wanita dengan Pengetahuan tentang Kesehatan Reproduksi di Puskesmas Tunjung Kecamatan Randuagung Kabupaten Lumajang Jawa Timur - Alya Kirana, Deifa Syaldillah; Sukarya , Wawang Setiawan; Pudyastuti , Erlina (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2024)
The maternal mortality rate in Indonesia is still high at 4,400/100,000 births, likewise in Lumajang Regency at 97/100,000 live births. Various factors that influence the high maternal mortality rate include knowledge about reproductive health. In Lumajang Regency there is a regent's regulation about prospective bride and groom must report to the Puskesmas to obtain reproductive health information. Until now, in the coverage area of Tunjung Health Center, Lumajang Regency are not known about the connection between characteristics of the prospective bride and groom with knowledge about reproductive health, this research was conducted to find out. An observational analytic survey with cross sectional approach are used in this research. Fifty research samples were determined by the Lemeshow formula and total sampling technique. Data were collected using questionnaire that was created and validated. The results showed that most of the prospective brides were aged 20 to 35 years (63.64%), while the risk group in terms of age <20 years was 36.36%. Most of education of the bride-to-be is in junior high school (52.73%) and 12.73% are elementary school. The highest income for prospective brides is under 2 million (69.09%) with 14.55% of them earning below 1 million. Sourcemost reproductive health information from teachers (47.27%) and parents (21.82%), the respondent group of prospective brides with less knowledge are only 5.45%. The results of statistical analysis with Pearson chi-square test showed there is a significant relationship between age and the level of knowledge of reproductive health. Keywords: age, education, income, reproductive health